Economic Globalisation, Democracy and Income in Sub-Saharan Africa: A Panel Cointegration Analysis - Daniel Sakyi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Sub-Saharan Africa has been characterised by low-income levels for decades. This paper analyses the impact of economic globalisation and democracy on income in sub-Saharan Africa using panel cointegration techniques. The paper considers a composite indicator for economic globalisation and several alternative indicators of democracy and highlights the essence of the simultaneous adoption of economic globalisation and democracy for sub- Saharan African countries. The empirical results based on a sample of 31 countries over the 1980-2005 period, clearly indicate that, whilst the total long run impact of economic globalisation on income has been beneficial, the total long run impact of democracy has been the bane of income in sub-Saharan Africa. The paper concludes that policy reforms should aim to improve democratic institutions in sub-Saharan Africa for its potential benefits to be realised.
Keywords: P0; E0; O1; O55; 330; Economic Globalisation; Democracy; Income; Sub-Saharan Africa